The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018 IEEE International Symposium on Circuits and Systems (ISCAS) 2018
DOI: 10.1109/iscas.2018.8351766
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Efficient CMOS Memristive Synapses for Mixed-Signal Neuromorphic System-on-a-Chip

Abstract: Emerging non-volatile memory (NVM), or memristive, devices promise energy-efficient realization of deep learning, when efficiently integrated with mixed-signal integrated circuits on a CMOS substrate. Even though several algorithmic challenges need to be addressed to turn the vision of memristive Neuromorphic Systems-on-a-Chip (NeuSoCs) into reality, issues at the device and circuit interface need immediate attention from the community. In this work, we perform energy-estimation of a NeuSoC system and predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…However, the fundamental limitation of such architectures was that the weights were dynamically stored and updated on capacitors, which leak away in a few milliseconds, limiting any long-term learning [16,17]. Bistability of analog weights has been used as an intermittent solution for long-term storage of weights [16,[18][19][20][21][22][23][24]. However, recent studies on deep SNNs have determined that at least 4-bit resolution is needed for the synaptic weights to attain classification accuracy comparable to conventional deep learning [25,26].…”
Section: Subthreshold Analog Neuromorphic Platformsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the fundamental limitation of such architectures was that the weights were dynamically stored and updated on capacitors, which leak away in a few milliseconds, limiting any long-term learning [16,17]. Bistability of analog weights has been used as an intermittent solution for long-term storage of weights [16,[18][19][20][21][22][23][24]. However, recent studies on deep SNNs have determined that at least 4-bit resolution is needed for the synaptic weights to attain classification accuracy comparable to conventional deep learning [25,26].…”
Section: Subthreshold Analog Neuromorphic Platformsmentioning
confidence: 99%
“…The author also introduced a first compact CMOS memristor emulator circuit [47,48] and the resulting dynamic synapse circuits [24] but concluded that non-volatile synapses are needed for long-term retention of weights, high synaptic density and low leakage power in trained neural networks. Consequently, the Neuromorphic computing architecture development requires synergistic development in devices, circuits and learning algorithms to take advantage of the high synaptic density while not being oblivious to the challenges at the device-circuit interface.…”
Section: Nanoscale Emerging Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The author also introduced a first compact CMOS memristor emulator circuit [23,24], and resulting dynamic synapse circuits [25] but concluded that non-volatile synapses are needed for long-term retention of weights, high synaptic density, and low leakage power in trained neural networks. Consequently, the Neuromorphic computing architecture development requires synergistic development in devices, circuits and learning algorithms to take advantage of the high synaptic density while not being oblivious to the challenges at the device-circuit interface.…”
Section: Nanoscale Emerging Devicesmentioning
confidence: 99%